Elucidating encounters of atypical ductal hyperplasia arising in gynaecomastia. Issue 3 (25th November 2014) - Wells, Justin M; Liu, Yifang; Ginter, Paula S; Nguyen, Michaela T; Shin, Sandra J
<x xml:space="preserve">Abstract</x> Aims Atypical ductal hyperplasia (ADH) rarely arises in gynaecomastia. We set out to understand more clearly the clinical, histological and immunohistochemical features of ADH in this setting. Methods and results Twenty‐five cases of ADH arising in gynaecomastia, nine cases of ductal carcinoma in situ (DCIS) and 36 cases of gynaecomastia with usual ductal hyperplasia (UDH) were studied. Reviews of clinical, morphological and immunohistochemical findings were performed. The extent of cytokeratin 5/6 (CK5/6) luminal epithelial cell staining was assessed (0% = 0, <10% = 1, 10–50% = 2 and >50% = 3). Oestrogen receptor (ER) was evaluated using the H‐scoring system. The average age of ADH patients was 35 years (range 14–78). ADH was bilateral in 20% and less frequent in active gynaecomastia (24%). ADH often showed a cribriform pattern (72%), with less nuclear variation/size and similar frequency of mitoses than UDH cells. CK5/6 luminal epithelial staining was decreased in ADH (68%) versus UDH (11%). ADH showed high ER expression compared to UDH (H score >270 in 88% and 14%, respectively). Conclusions ADH in gynaecomastia can be distinguished from UDH by morphological and immunhistochemical features. We also identified a subset of young patients (<25 years) with extensive bilateral ADH. More studies are needed to characterize this patient subset more clearly.